The Impact of Omega-3 Fatty Acids on the Most Common Cardiovascular Diseases – A Literature Review - Dąbek, Jakub; Wiśniewska, Aleksandra; Kosucka, Wiktoria; Balik, Dominik; Lara, Joanna; Grabowska, Martyna; Grabowska, Karolina; Kwaśniewska, Anna; Kaszyńska, Karolina; Kubicka, Jagoda (Quality in Sport, 2025)
Background Epidemiological data suggest a beneficial effect of omega-3 fatty acids on cardiovascular risk. Aim of the study The aim of this literature review is to compile currently available studies and examine the mechanisms of action of omega-3 fatty acids and their application in the most common cardiovascular diseases, such as hypertension, coronary artery disease, atrial fibrillation, and heart failure. The article also analyzes the relationship between clinical and therapeutic effects and factors such as dose, the presence of cardiovascular diseases, and the population under study. Material and methods Literature available in the PubMed database was reviewed using the following keywords ,,Omega-3” ,,fish oil” ,,hypertension” ,,heart artery disease” ,,cardiovascular risk” ,, cardiovascular diseases” ,, heart diseases” ,, cardiovascular outcomes” ,,heart failure” ,,anti-inflammatory” Conclusion This literature review suggests that omega-3 fatty acids may improve treatment outcomes in certain cardiology patients. Clinical effects are dose-dependent, and influenced by the duration of supplementation as well as the population in which they are applied. Regardless of the dose, omega-3 fatty acids do not reduce cardiovascular risk; however, their addition to therapy in patients already undergoing cardiological treatment may offer benefits. Higher doses may exert hypotensive effects, significantly reduce hypertriglyceridemia, and improve left ventricular ejection fraction, although they are associated with an increased risk of atrial fibrillation.